2018
DOI: 10.1007/s40257-018-0387-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Topical Combination of 0.25% Finasteride and 3% Minoxidil Versus 3% Minoxidil Solution in Female Pattern Hair Loss: A Randomized, Double-Blind, Controlled Study

Abstract: clinicaltrials.in.th; identifier TCTR20160912002.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 18 publications
1
49
0
Order By: Relevance
“…AGA is a non-scarring alopecia in which terminal hairs transform into miniaturized hairs. Typically in men, baldness occurs with frontal recession and vertex thinning,26 while in women, hair loss is characterized by a decrease in hair density over the crown without frontal hairline involvement, also known as female pattern hair loss (FPHL) 27. Testosterone plays a role in AGA pathogenesis following conversion to dihydrotestosterone (DHT) by 5-alpha reductase 28,29…”
Section: Use Of Minoxidil In Hair Disordersmentioning
confidence: 99%
“…AGA is a non-scarring alopecia in which terminal hairs transform into miniaturized hairs. Typically in men, baldness occurs with frontal recession and vertex thinning,26 while in women, hair loss is characterized by a decrease in hair density over the crown without frontal hairline involvement, also known as female pattern hair loss (FPHL) 27. Testosterone plays a role in AGA pathogenesis following conversion to dihydrotestosterone (DHT) by 5-alpha reductase 28,29…”
Section: Use Of Minoxidil In Hair Disordersmentioning
confidence: 99%
“…Several studies performed on Asians reported a lower prevalence of AGA and FPHL compared with the Europeans. [49][50][51][52] The development of AGA in Japanese men is approximately 10 years slower than that in Europeans, with 1.4-times lower in prevalence in each decade. 51 By contrast, the prevalence of AGA in Thais is higher and relatively similar to Caucasians, suggesting that the prevalence may be influenced by various genetic backgrounds.…”
Section: Non-scarring Alopecias In Asiansmentioning
confidence: 99%
“…Of the seven included studies, three 21,22,24 reported the clinical efficacy in terms of hair count increase, with a total of 99 patients. We used random effect model in analysis with high heterogeneity ( I 2 > 50%) among the three trials.…”
Section: Resultsmentioning
confidence: 99%